Crypto decrypted : debunking myths, understanding breakthroughs, and building foundations for digital asset investing - Ryan, Jake (Financial advisor); Diorio, James M., Jr (John Wiley & Sons, Inc., 2023)
"What are is the big breakthrough? It's called the Merge and its purpose is to transform Ethereum, which is the most-used blockchain and powers Ether, the second-largest cryptocurrency, with a $202 billion market cap. Ethereum also hosts numerous decentralized applications (dApps) and decentralized finance (DeFi) protocols and establishes the authenticity of millions of non-fungible tokens (NFTs). This means the outcome of the merge will affect not just the Ethereum blockchain, but a wide constellation of products and services that rely upon it. And given Ethereum's size and influence, the fate of the merge is likely to have a ripple effect on the broader crypto industry. The switch from proof of work to proof of stake will reduce overall energy consumption of Ethereum by 99.9% or more. That's game changing. Also, on Ethereum's road map are four other phases happening in parallel that developers are calling the "surge, verge, purge, and splurge"--all of which aim to make Ethereum much faster, safer, and more decentralized. At the end of this road map, Ethereum will be able to process 100,000 transactions per second. Again, this speed and scale may alter the world of financial services"--